Optimizing Digital Literacy to Elevate Graduate Quality in Islamic Junior High Schools - Marwani; Norman, Efrita (Journal of Educational Management Research, 2025)
This study examines the management of digital literacy programs at SMP Plus Ulil Albab Cirebon, an Islamic junior high school, using a qualitative case study approach. It focuses on how key managerial functions—planning, organizing, implementing, and supervising—are applied to integrate digital literacy in a systematic and ethical manner. Data collection included interviews, observations, and document analysis. The findings show that digital literacy is seen not just as a technical skill but as a transformative process aligned with the school’s religious values and educational mission. Strategic planning incorporates both national and global education frameworks; organizational structures foster distributed leadership; instructional practices emphasize constructivist and value-based approaches; and supervision encourages collective reflection. The program has boosted student agency, digital ethics, and the school’s learning culture, although challenges remain, such as infrastructure limitations and varying teacher digital competence. This study offers an ethical, contextually relevant model for managing digital literacy in faith-based schools, providing valuable insights for educational policy, school leadership, and curriculum development in the digital age.